Money well spent? the truth behind the trillion-dollar stimulus, the biggest economic recovery plan in history - Grabell, Michael (PublicAffairs, 2012)
Traces the evolution of the American Recovery and Reinvestment Act of 2009 while offering insight into its fiercely partisan supporters and detractors, explaining how the money was spent and what will be the most likely outcome.